Characterization of bronchus-associated lymphoid tissue induced by co-exposure to Asian sand dust and ovalbumin: a study using 3D serial section imaging - Mikami, Yoshikazu; Hayatsu, Manabu; Kuroda, Etsushi; Tsuda, Hiromasa; Toriumi, Taku; Mizutani, Yusuke; Ichinose, Takamichi; Honda, Akiko; Takano, Hirohisa (Frontiers in Immunology, 2025)
IntroductionInducible bronchus-associated lymphoid tissue (iBALT) develops with different morphologies and functions depending on the type of antigen, in which various cytokines, such as interleukin (IL)-1 and IL-17, and the cells producing them, such as T helper 17 (Th17) and T follicular helper (Tfh) cells, play an important role. We recently observed that numerous inflammatory cells, mainly B cell like-cells forming peribronchial clusters, accumulate in the lungs of mice exposed to Asian sand dust (ASD), suggesting that ASD induced iBALT development. However, whether ASD induced iBALT formation, much less the mechanism by which ASD promotes iBALT formation, remains unknown.MethodsB cell clusters were analyzed using the next generation serial section-three-dimensional (nSS3D) imaging method, in which we attempted to introduce batch image acquisition using a high-resolution slide scanner and AI-based image registration and target extraction. Furthermore, the mechanism underlying ASD-induced B-cell cluster formation was examined using CD4-Cre Bcl6f/f mice lacking Tfh cells.ResultsASD induced B-cell cluster formation in mouse lung tissue, which was enhanced by allergen (Ovalbumin: OVA) exposure. Furthermore, the nSS3D images revealed that a part of the B cell clusters induced by OVA+ASD but not others exhibited common histological features of previously reported iBALTs. Moreover, OVA+ASD exposure failed to induce all of the B cell cluster formation including iBALTs in CD4-Cre Bcl6f/f mice.ConclusionB cell clusters including iBALTs are induced by ASD; this process is enhanced by OVA, in which Tfh cells were suggested to play important roles. Characterization of the OVA+ASD-induced B cell clusters proved that the SS3D technique is useful for the analysis of mouse disease models. The results also emphasize the need for medical countermeasures for patients with allergic diseases living in areas with ASD contamination.